Ideal Student Prototype: A Cognitive Linguistic Study - Rifai, Muhamad Husain; Baking, Aad Nur Sayyidus Syuhuur; Hasanah, Ummi; Zakaria, Alif; Wulandari, Betty Ayunda (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to describe the ideal student prototype within the Ideal Cognitive Model (ICM), which can represent the conceptual knowledge of an ideal speaker without excluding other concepts. The study is based on cognitive linguistic analysis, examining how the human mind shapes speech. The term “Ideal Student” does not yet have a definition that accurately captures its meaning due to the many individual perceptions and diverse categories people use to define it. As a result, the concept has developed into various prototypes. In this study, the researcher provided commonly spoken concepts, and respondents selected those that matched their own cognition of the term “ideal student.” The collected data were then classified and analyzed to identify the ideal meaning within their cognition, using Lakoff's prototype theory. The results are presented in the form of tables and model explanations. The analysis concludes that the top three models within the ideal student prototype are having many soft skills, being diligent, and being active in organizations.